‘Prescription’ for Purposeful Adaptation of Professionalism-and-Ethics Teaching Strategies for Remote Delivery - Cicely Roche (Pharmacy, 2021)
This case report outlines the strategies underpinning the adaptation of professionalism and ethics strand (P&E) teaching for remote delivery on a Pharmacy programme in response to COVID-19 restrictions. In line with national and University guidance, P&E teaching detailed in this report was delivered online in late 2020. Sessions were generally live and recorded, although some content was pre-recorded using video-capture software. All learning activities, recordings and supporting resources are accessible to students on the University’s Virtual Learning Environment. This report reflects on the curriculum, pedagogy and content of P&E teaching, with particular emphasis on teaching related to professional identity formation and moral reasoning competencies development. Design, development and delivery of remote online teaching is considered in the context of P&E teaching. Strategies used to plan for adaptation and delivery of interactive online teaching sessions aligned with P&E teaching are described. Key findings support a scholarship of teaching approach when planning for adaptation to remote online teaching. Purposeful consideration of existing curricular, pedagogical and instructional design enables the teacher to identify critical P&E teaching activities potentially compromised by the move to the online environment. Informed integration of available instructional tools to teaching activities follows. The report concludes with recommendations for future research.